2023
DOI: 10.1101/2023.09.05.556382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A genetic screen identifies a role foroprFinPseudomonas aeruginosabiofilm stimulation by subinhibitory antibiotics

Luke N. Yaeger,
Michael R. M. Ranieri,
Jessica Chee
et al.

Abstract: Biofilms are surface-associated communities of bacteria that grow in a self-produced matrix of polysaccharides, proteins, and extracellular DNA (eDNA). Sub-minimal inhibitory concentrations (sub-MIC) of antibiotics induce biofilm formation, indicating a potential defensive response to antibiotic stress. However, the mechanisms behind sub-MIC antibiotic-induced biofilm formation are unclear. We show that treatment ofPseudomonas aeruginosawith multiple classes of sub-MIC antibiotics with distinct targets induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Following up on our discovery that a P. aeruginosa oprF mutant is hypersensitive to TMP 27 , we found that this mutant is also hypersensitive to SUL ( Fig 2a ). We next tested the ability of TMP to compromise envelope integrity using the classic method of exposing cells to hyper- or hypo-osmotic stresses.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Following up on our discovery that a P. aeruginosa oprF mutant is hypersensitive to TMP 27 , we found that this mutant is also hypersensitive to SUL ( Fig 2a ). We next tested the ability of TMP to compromise envelope integrity using the classic method of exposing cells to hyper- or hypo-osmotic stresses.…”
Section: Resultsmentioning
confidence: 83%
“…We previously discovered that a P. aeruginosa oprF mutant was hypersensitive to TMP, suggesting a possible link between folate and PG metabolism 27 . OprF is a major outer membrane porin with a C-terminal PG-binding domain that anchors the outer membrane to the cell wall 28 .…”
Section: Resultsmentioning
confidence: 99%